2021
DOI: 10.1007/s00415-021-10502-z
|View full text |Cite
|
Sign up to set email alerts
|

Is postural orthostatic tachycardia syndrome (POTS) a central nervous system disorder?

Abstract: Postural orthostatic tachycardia syndrome (POTS), a disorder of the autonomic nervous system characterized by a rise in heart rate of at least 30 bpm from supine to standing position, has been traditionally viewed as a dysfunction of the peripheral nervous system. However, recent studies and evidence from overlapping conditions suggest that in addition to being considered a disorder of the peripheral nervous system, POTS should be viewed also as a central nervous system (CNS) disorder given (1) significant CNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
0
12
0
2
Order By: Relevance
“…Patients with POTS have been shown to have a higher prevalence of specific autoantibodies (AAbs), including G-Protein coupled receptor (GPCR) antibodies, which could explain an increase in sympathetic tone by activating adrenergic receptors and eliciting a negative allosteric effect on muscarinic GPCRs [74,75]. These serum patterns have been confirmed in COVID-19 survivors with dysautonomia [57] and are comparable to those seen in patients with CFS and small-fiber neuropathy [56]. A severe orthostatic intolerance syndrome was reported in a young lady with previous COVID-19 infection who was later diagnosed with small-fiber neuropathy and who responded well to the administration of intravenous immunoglobulins, thus suggesting an autoimmune trait likely caused her symptoms [51].…”
Section: How Does Sars-cov-2 Infection Cause Long-term Dysautonomia?mentioning
confidence: 82%
See 2 more Smart Citations
“…Patients with POTS have been shown to have a higher prevalence of specific autoantibodies (AAbs), including G-Protein coupled receptor (GPCR) antibodies, which could explain an increase in sympathetic tone by activating adrenergic receptors and eliciting a negative allosteric effect on muscarinic GPCRs [74,75]. These serum patterns have been confirmed in COVID-19 survivors with dysautonomia [57] and are comparable to those seen in patients with CFS and small-fiber neuropathy [56]. A severe orthostatic intolerance syndrome was reported in a young lady with previous COVID-19 infection who was later diagnosed with small-fiber neuropathy and who responded well to the administration of intravenous immunoglobulins, thus suggesting an autoimmune trait likely caused her symptoms [51].…”
Section: How Does Sars-cov-2 Infection Cause Long-term Dysautonomia?mentioning
confidence: 82%
“…Hypovolemia has been widely recognized in PASC patients with dysautonomic features [25,52]. Hypovolemia may trigger hyperadrenergic POTS and lead to cerebral hypoperfusion and the impairment of central autonomic networks [56]. Preliminary evidence on post-COVID POTS supports the correction of hypovolemia by the liberal intake of water and salt [16] and other nonpharmacological interventions aimed at intravascular volume expansion and increasing venous return [65] (Figure 1).…”
Section: How Does Sars-cov-2 Infection Cause Long-term Dysautonomia?mentioning
confidence: 99%
See 1 more Smart Citation
“…44 Since the onset of the COVID-19 pandemic, an increasing number of case reports about the occurrence of POTS secondary to a COVID-19 infection have emerged. [24][25][26][27][28][29][30] Several hypotheses about possible pathomechanisms of POTS or dysautonomia in general after COVID-19 infection have been proposed: imbalance of the renin-angiotensin-aldosterone system, 26,29 brainstem involvement, 43,45,46 autoreactivity to antibodies against SARS-CoV-2, 25,43,47 dyshomeostasis of immune response 42,44 and denervation of peripheral sympathetic nerve fibers. 26,43,42 This study has some limitations.…”
Section: Muscle Painmentioning
confidence: 99%
“…POTS' diagnosis is made by the tilt test or a 10-minute support test, in which characteristically occurs an increase in heart rate of at least 30 bpm from the supine position to the upright position without orthostatic hypotension, in association with pre-syncope symptoms and orthostatic intolerance [4,9,10]. Lately, few studies have reported the occurrence of POTS after COVID-19 infection [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%